Unacknowledged legislation : writers in the public sphere / Christopher Hitchens. - Hitchens, Christopher, 1949- (Verso, 2000)
Many see the encounter between literature & politics as fraught. This text offers a different approach, showing that whilst the engagement between writers & those in power isn't always smooth, it generally embodies a dialectic worth investigation.